The Effect of Nutritional Status and Lighting on the Incident Pulmonary Tuberculosis in Padangsidimpuan City - Suryani Suryani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Pulmonary tuberculosis (TB) is still a global health problem, this disease is directly transmitted caused by Mycobacterium tuberculosis. The purpose of this study was to analyze the effect of nutritional status and lighting on the incidence of pulmonary TB in Padangsidimpuan City. This study is an analytical observational study with a case-control design. The sample consisted of 56 cases and 56 controls. The analysis used simple logistic regression and multiple logistic regression tests. The results of the logistic regression test showed a significant effect between nutritional status (p = 0.041; OR = 2.906, 95% CI 1.045-8.081) and lighting (p = 0.048; OR = 2.995, 95% CI 1.008-8.902) on the incidence of pulmonary TB. It is recommended to maintain body health by consuming nutritious food and paying more attention to the physical environment of the house, especially lighting so that sunlight enters the house.